Synthetic Cannabinoid Use and Descriptive Norms among Collegiate Student-Athletes - Egan, Kathleen L. (J Psychoactive Drugs, 2016)
Synthetic cannabinoids have gained popularity over the past decade, especially among young adults, due to sharing similar psychoactive properties with Tetrahydrocannabinol (THC). A limited number of studies have examined synthetic cannabinoid use among college students but none have examined use exclusively by collegiate student-athletes. The objective of this study was to examine synthetic cannabinoid use among collegiate student-athletes. In the spring of 2013, 3,276 freshmen and transfer collegiate student-athletes from 47 NCAA Division I, II, and III institutions participated in a web-based survey on substance use. Bivariate logistic regression was used to analyze the relationship between collegiate student-athlete characteristics, substance use, and descriptive norms with lifetime use of synthetic cannabinoids. Sixty-two individuals (1.9%) reported lifetime use of synthetic cannabinoids, and 3 (0.1%) reported past-30-day use. Males, current drinkers, and athletes who used hookah and marijuana in the past 30 days were more likely to use synthetic cannabinoids. Peer use of synthetic cannabinoids was estimated to be higher than actual use, and such overestimation was positively associated with personal use of synthetic cannabinoids. Our findings suggest that campaigns addressing normative beliefs should be implemented on college campuses to prevent synthetic cannabinoid use among college students and collegiate student-athletes.